Epigenetics of the molecular clock and bacterial diversity in bipolar disorder. (March 2019) - Bengesser, S.A.; Mörkl, S.; Painold, A.; Dalkner, N.; Birner, A.; Fellendorf, F.T.; Platzer, M.; Queissner, R.; Hamm, C.; Maget, A.; Pilz, R.; Rieger, A.; et al.
Highlights: Methylation of the clock gene ARNTL (cg05733463) correlated negatively with bacterial diversity and evenness in Bipolar Disorder. Abstract: Objectives The gut microbiome harbors substantially more genetic material than our body cells and has an impact on a huge variety of physiological mechanisms including the production of neurotransmitters and the interaction with brain functions through the gut-brain-axis. Products of microbiota can affect methylation according to preclinical studies. The current investigation aimed at analyzing the correlation between gut microbiome diversity and the methylation of the clock gene ARNTL in individuals with Bipolar Disorder (BD). Methods Genomic DNA was isolated from fasting blood of study participants with BD (n = 32). The methylation analysis of the ARNTL CG site cg05733463 was performed by bisulfite treatment of genomic DNA with the Epitect kit, PCR and pyrosequencing. Additionally, DNA was extracted from stool samples and subjected to 16S rRNA sequencing. QIIME was used to analyze microbiome data. Results Methylation status of the ARNTL CpG position cg05733463 correlated significantly with bacterial diversity (Simpson index: r = -0.389, p  =  0.0238) and evenness (Simpson evenness index: r = -0.358, p  =  0.044). Furthermore, bacterial diversity differed significantly between euthymia and depression ( F( 1, 30 )  = 4.695, p  =  0.039). Discussion The results of our pilot study show that bacterial diversity differs between euthymia and depression. Interestingly, gut microbiome diversity and evenness correlate negatively with methylation of ARNTL, which is known to regulate monoamine oxidase A transcription. We propose that alterations in overall diversity of the gut microbiome represent an internal environmental factor that has an epigenetic impact on the clock gene ARNTL which is thought to be involved in BD pathogenesis.